2013
DOI: 10.1002/adma.201204458
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Colloidal Morphologies by Critical Casimir Forces

Abstract: Active control over the assembly of colloidal and nanoparticles has important applications for the design of new nanostructured materials, but it is a difficult task. Here, a new method is presented to control the morphology of colloidal aggregates using critical Casimir forces. Via direct temperature control of critical Casimir forces, the particles are assembled into aggregates with well-defined architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 19 publications
1
40
1
Order By: Relevance
“…Aggregation of colloids in a near-critical binary solvent has been studied experimentally on the ground and under microgravity conditions [68,85,194,195]. intensity I(q, t) revealed that I(q, t) exhibits a maximum at q = q * (t), which corresponds to the inverse of the mean cluster size.…”
Section: F Aggregation Kinetics and Structures Of Aggregatesmentioning
confidence: 99%
“…Aggregation of colloids in a near-critical binary solvent has been studied experimentally on the ground and under microgravity conditions [68,85,194,195]. intensity I(q, t) revealed that I(q, t) exhibits a maximum at q = q * (t), which corresponds to the inverse of the mean cluster size.…”
Section: F Aggregation Kinetics and Structures Of Aggregatesmentioning
confidence: 99%
“…The composition of solvent 2 is still sufficiently close to the critical one that critical density fluctuations occur. 6,10,18 The chosen experimental systems have the advantage that the particle refractive index matches that of the solvent, allowing direct imaging of particles and determination of g(r) deep in the bulk of the suspension. The particles are dyed, allowing us to image them under fluorescent illumination.…”
Section: A Colloidal System and Potential Measurementmentioning
confidence: 99%
“…We investigate two well-characterized systems 10,18 of poly-n-isopropyl acrylamide (PNIPAM) particles with a diameter of σ = 500 nm suspended in a near-critical quasi binary solvent composed of 3-methyl pyridine (3MP), water, and heavy water. 19,20 The two systems differ only in the relative mass fractions w x of the solvent components x (x = 3MP, H 2 O, D 2 O), as shown in Table I.…”
Section: A Colloidal System and Potential Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the theoretical side is concerned, it was de Gennes who first obtained the CCF between spherical particles [53] considering a local freeenergy functional. Among the other techniques used to study the CCF in sphere-plate and sphere-sphere geometries are the Ornstein-Zernike theory [54], conformal invariance methods [55][56][57], Monte Carlo calculations [58][59][60][61][62][63][64][65][66][67], fluid-particle dynamics simulations [68,69], mean-field type [70][71][72][73][74] and density-functional [75] theory calculations combined with the Derjaguin approximation [44,[76][77][78]. Several review articles and works [8,[79][80][81][82] summarize both the experimental and theoretical results presented there.…”
Section: Introductionmentioning
confidence: 99%